Applying a transdisciplinary mixed methods research design to explore sustainable diets in rural South Africa - Claasen, Nicole; Covic, Namukolo M.; Idsardi, Ernst F.; Sandham, Luke A.; Gildenhuys, Anél (University of Alberta, International Institute for Qualitative Methodology, 2015)
This article describes a conceptual framework for exploring sustainable diets, using a case study example of ongoing research in the Vaalharts region, a rural setting in South Africa. A qualitative research approach is followed with an integrated transdisciplinary mixed methods research design with multiple concurrent components employed during two sequential phases. A successful application of the framework is achieved through a collaborative team effort of researchers with qualitative and quantitative research expertise transcending different disciplines, as well as participation of community members throughout the research process. We demonstrate that transdisciplinary mixed methods research designs are essential to gain a better understanding of the complex concept of sustainable diets.
Keywords: Sustainable diets; mixed methods; case study; transdisciplinary research; South Africa